IDENTIFY THE CONTRIBUTORY FACTORS AND PREVALENCE OF OBESITY AMONGCHILDREN IN SELECTEDSCHOOLS, PUDUCHERRY. (CAHIERS MAGELLANES-NS, 2024)
Background: Nutritious foods help us to maintain good health. Consumption of healthy foods in abalanced form help us to minimize the health-related problems. Obesity among children andadolescents has adverse consequence onpremature mortality, and physical morbidity in adulthood andis associated with impaired health during childhood. The risk factors of obesity and overweightexplored from different studies revealed that, the genetic history, physical activity, high birth weight,and type of milk intake during infancy, morethan two hours of television watching per day, frequencyof regular meals and overweight of the parents. The purpose of the study was to identify the contributoryfactors and prevalence of obesity among childrenObjectives: To assess the level of obesity among selected school children at Puducherry. To identifythe contributory factors leading to obesity To associate the pretest level of obesity with selecteddemographic variables of school children at Puducherry.Materials And Methods: The quantitative research approach was selected and non-experimentaldescriptive research design was used. The study was conducted among 1062 school children studying8th and 9th standard in selected Government and Private schools at Puducherry In this study, clustersampling technique was used to select the schools and Non probability – convenient sampling techniquewas used to assess the obesity. Totally six schools were selected and sampling frame was made. Datacollection tool was consisting of three sections and validated by the subject experts. Obtained ethicalapproval to conduct the studyResults and conclusion: The prevalence of overweight and obesity was found to be 9.7% and 4.9%respectively. Key contributory factors identified include genetic history, physical activity, birth weight,milk type in infancy, television watching, meal frequency, and parental overweight.